2017
DOI: 10.1074/jbc.c117.775270
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyl Itaconate Is Not Metabolized into Itaconate Intracellularly

Abstract: Edited by Luke O'NeillItaconic acid is an important metabolite produced by macrophages after stimulation with LPS. the cell culture medium leads to elevated intracellular levels of unlabeled succinate, with no evidence of intracellular uptake. The goal of this study is to encourage the development of effective pro-drug strategies to increase the intracellular levels of itaconate, which will enable more conclusive analysis of its action on macrophages and other cell and tissue types.Itaconic acid is a dicarboxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
83
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(85 citation statements)
references
References 17 publications
1
83
1
Order By: Relevance
“…It is known that cytoplasmic esterases catalyze OI to produce itaconate. However, whether exogenous DI can be directly metabolized into itaconate in cells is still controversial . This highlights current limitations in the intracellular delivery of itaconate and emphasizes the development of effective prodrug strategies to precisely define its anti‐inflammatory function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is known that cytoplasmic esterases catalyze OI to produce itaconate. However, whether exogenous DI can be directly metabolized into itaconate in cells is still controversial . This highlights current limitations in the intracellular delivery of itaconate and emphasizes the development of effective prodrug strategies to precisely define its anti‐inflammatory function.…”
Section: Discussionmentioning
confidence: 99%
“…LPS‐tolerized wild‐type BMDMs that can produce substantial amounts of itaconate compared with IRG1‐deficient cells display a significant decrease in IL‐6 levels, suggesting that endogenous itaconate acts in a manner consistent with exogenous DI . However, a recent study showed that DI cannot be directly converted to itaconate, instead it promotes itaconate biosynthesis in LPS‐stimulated BMDMs . It is believed that DI is unlikely to mimic endogenous itaconate.…”
Section: Anti‐inflammatory Action Of Itaconatementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the exact mechanism of action of exogenously administered itaconate analogs, DMI and OI, is not clearly understood. It is postulated that these molecules might bind to the SUCNR1 receptor or other unknown cell surface receptor, leading to the observed effects …”
Section: Translational Relevance For Developing Novel Drugs Targetingmentioning
confidence: 99%
“…Furthermore, a study by El Azzouny et al. showed that cell‐permeable DMI is not metabolized to itaconate by mouse bone marrow‐derived macrophages and treatment with 13 C labelled DMI elevated intracellular succinate only, with no evidence of intracellular itaconate uptake . Therefore, suitable molecules aimed at modulating intracellular itaconate levels remain to be developed.…”
Section: Translational Relevance For Developing Novel Drugs Targetingmentioning
confidence: 99%